Analisis Strategi Guru Dalam Menerapkan Literasi Digital Pada Pembelajaran Kurikulum Merdeka Di SD Aisyiyah 1 Mataram - Astini, Baiq Ida; Aqodiah, Aqodiah; Hasanah, Niswatun (Universitas Muhammadiyah Mataram, 2025)
This study aims to examine the role of teachers in strengthening digital literacy in the implementation of the Merdeka Curriculum at SD ‘Aisyiyah 1 Mataram. The research method used was descriptive qualitative with data collection techniques including observation, interviews, and documentation. The results show that teachers play a strategic role in developing students' digital literacy skills through innovative and contextual learning methods, such as project-based learning. In addition to technical skills, teachers also instill digital moral values and ethics as an integral part of digital literacy. Challenges identified include limited technological infrastructure and restricted learning time. However, teachers strive to overcome these obstacles through collaboration and adaptation of learning methods according to student characteristics. This study provides important contributions to the development of a holistic and sustainable digital literacy learning model in elementary schools based on the Merdeka Curriculum.